Replanning Buildings In Surabaya Case Study of Office Buildings On Jalan Basuki Rachmat Surabaya - Fathony Maulidy, Ahmad; Oetomo, Wateno; Marleno, Risma (Green Publisher Indonesia, 2023)
Infrastructure development is an important aspect in boosting the economic growth of the Indonesian people, with the stages of infrastructure development which include building facilities and infrastructure can overcome economic inequality, the opening of new jobs, per capita income will increase. Referring to Law No. 28 of 2002 concerning building buildings in article 3 states that to realize a building that is functional and in accordance with the building layout that is harmonious and in harmony with the environment, it must ensure the reliability of the building in terms of safety, health, comfort and convenience. Problems: Based on the description above in the explanation in the background, the researcher formulated the following problem: How to plan a building structure that is strong in withstanding loading according to SNI 1726-2019 and SNI 2847-2013? How to plan building structures according to annual costs. The results of the planning of the Office Building on Jln Basuki Rachmat Surabaya as stated in Chapter IV, from the planning of the floor slab to the foundation in accordance with the elements in the 8-story Building Building and require a cost of Rp. 94,965,401,000, - and the implementation time takes 35 weeks or ± 8 calendar months.